Biology of Delia antiqua (Diptera: Anthomyiidae) on onion - Fatimah, Nusrat; Yaqoob, Munazah; Mir, Sajad Hussain (Indian Journal of Plant Protection, 2025)
The onion maggot fly, Delia antiqua, is a significant pest causing damage to onion crops. Understanding its biology and biometrics under laboratory conditions is crucial for developing effective management strategies. In this study, we investigated various biological aspects Delia antiqua in a controlled laboratory environment. The eggs laid by female D. antiqua are tiny, elongated and white-coloured. The maggotspass through three cream-coloured instars and develop into dark brown barrel shaped pupae. The adult flies resemble houseflies in shape and colour. Morphometric measurements of different life stages of D. antiqua revealed that the average length and breadth of egg measured 1.26±0.16 mm and 0.33±0.07 mm, respectively. The first, second and third instar maggots measured 3.56±0.21 mm, 7.12±0.45 mm and9.51±0.46 mm respectively in length and 0.71±0.21 mm, 0.87±0.07 mm and 1.44±0.17 mm respectively in breadth. Average length and breadth of pre-pupa and pupa was 7.63±0.15 mm, 1.47±0.14 mm and 4.67±0.57 mm, 1.78±0.07 mm, respectively. The mean length and breadth of adult male was 8.17±0.16 mm and 13.55±0.15 mm, whereas, the adult female measured 8.65±0.14 mm in length and 16.70±0.19mm in breadth. The egg, total maggot, pre-pupal and pupal period lasted for 2.7±0.45 days, 16.5±1.02 days, 2.1±0.71 days and 14.7±0.48 days, respectively. The pre-oviposition, oviposition and post-oviposition period had an average value of 5.3±0.46 days, 15.8±1.07 days and 2.8±0.87 days, respectively. Fecundity of the female was on an average about 244.9±16.69 eggs. Sex ratio (male: female) was recorded as 0.98±0.36. Adult male and female longevity was 18.1±0.83 days and 23.3±0.78 days, respectively. The total life cycle from egg to adult emergence varied from 57 to 61 days.